THE IMPACT OF GREEN SUPPLY CHAIN MANAGEMENT (GSCM) PRACTICES ON FIRM PERFORMANCE - Zakiah Syamra Suhaimi; Jevitha Chandran, (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
The heightened awareness of environmental sustainability has prompted organizations, particularly within the manufacturing industry, to revaluate their supply chain management (SCM) practices. Hence, this study explores the relationships between green supply chain management (GSCM) practices and firm performance. Survey data collected from 320 Malaysian manufacturers were used to conduct correlation analysis. Overall, results show that the adoption of GSCM practices enhances environmental and financial performances. Implementation of GSCM practices is an important aspect of manufacturing operations strategy as they help manufacturers not only improve environmental performance but also increase profitability.